GREEN INTELLECTUAL CAPITAL AND ENVIRONMENTAL MANAGEMENT ACCOUNTING: A LITERATUR REVIEW - Niken Safitri; Nurmala Ahmar; Muhammad Zaky; Moh. Ali Rahmani (Jurnal Proaksi, 2022)
In the last two decades, the "going green" aspect has been identified as the main motivation for organizations to improve the competitiveness of enterprises. Likewise with one of the company's intangible assets, namely intellectual capital. Green Intellectual Capital is an effective tool to improve company performance and also business continuity. This research uses a review of various literaturs on EMA and GIC. Where the samples in this research are articles from the last 4 years in the form of 22 researches taken from several electronic databases such as Proquest, Google Scholar, Open New Knowledge. The results of this research provide empirical evidence regarding EMA and GIC, especially in manufacturing companies. Based on the research results in this study, EMA and GIC have a positive effect on competitive advantage, sustainable performance, Green human resource management Financial Performance, green supply chain performance environment performance. This research aims to conduct an empirical study of research on EMA and GIC associated with several variabels such as competitive advantage, sustainable performance. Keywords: Green Intellectual Capital, EMA